Assessment of proper use of Metered Dose Inhaler among patients attending the Out Patient Department of Respiratory Medicine: a cross sectional study - Das, Dipyaban; Meena, Kavita; Sinha, Debopriyo; Dey, Bitwadru; Biswas, Debabrata; Haldar, Atanu; Mukhopadhyay, Debjotiy; Banerjee, Chirantan; Paul, Dipanjali; Biswas, Debasmita; Mondal, Jayanti; Mandal, Kabita; et al. (The ESRF Research Journal for Undergraduate Medical Students, 2023)
IntroductionRespiratory inhalers are the backbone of asthma and COPDmanagement, targeting drug delivery directly to the airways(target zone).However, inhalers are very often used sub-optimally leading to uncontrolled symptoms and increased drugutilization for relief medication or preventative therapy, thereby increasing the prescription costs for patients.Objectives:Tofind out the socio demographic profile,disease characteristics, type of MDI used and assessing the correct stepsofusage of MDI among patients, attending Respiratory Medicine Outpatient Department of Nil Ratan Sircar Medical College,Kolkata.Materials and methods:An institutional based observational descriptive study with cross sectional design, was carried out, among 115 patientsusing MDI,>12 years attending respiratory OPD during the study period were included in the study. Data were collectedusing a predesigned and pretested schedule, entered into MS excel, cleaned and analysed with SPSS (IBM SPSS version20). Approval was taken from Institutional Ethics Committee.ResultsThe mean (standard deviation) age of the study population was 50 (14.5) years. Almost 53%(52.2%) of the patients wereusing steroid inhalers, 47.2 % of them for > 12 months. Most (93%) had been demonstrated by the treating physician. Only13% perceived difficulty in MDI use. The common mistakes made by the patients during MDI use were the following;13.9% sealed the mouth around the inhaler, 29.6% continued breathing after pressing the MDI and 38.3% rinsed theirmouth after using steroid inhaler.ConclusionsSeveral mistakes are committed by the users of MDI during the process, almost all of which can be minimized by repeatedinstructions and supervision of MDI technique by the treating physician. Proper MDI use will decrease drug wastageleading to better and cheaper management of symptoms.